Evaluation of corrosion inhibition at sand-deposited carbon steel in CO2-saturated brine - Pandarinathan, V.; Lepkova, Katerina; Bailey, Stuart; Gubner, Rolf (Pergamon, 2013)
The adsorption of four CO2 corrosion inhibitors on silica sand and their subsequent inhibition activity at sand-deposited steel has been investigated. The presence of a sand deposit affects the performance of inhibitors at carbon steel due to their competitive adsorption on sand. Sulfur-containing organic compounds show minimal adsorption on sand compared to pyridinium surfactants and provide the highest inhibition efficiency at the sand-deposited steel. The extent of inhibitor adsorption onto sand is discussed in relation to their chemical structures. The significance of determining the adsorption affinity to sand in the selection of inhibitors to mitigate under-deposit corrosion is demonstrated